Pozytywiści warszawscy wobec tradycji. Stan badań, postulaty badawcze - Markiewicz, Grzegorz (Acta Universitatis Lodziensis. Folia Historica, 1995)
In scientific literature Warsaw positivism as an ideological trend is opposed to Romanticism and is perceived as the programme of practical activity breaking with the past and calling for active work on the social and economic field. Warsaw positivists’ attitude towards tradition was reflected in literature on that subject which distinguished two opposing attitudes. On one hand there was a radical attitude directed against tradition and negating it in the name of progress. On the other hand there was a moderate attitude appreciating the importance of tradition and the values it carried waith itself. It is also stressed that arguments over tradition contented on the columns of positivist press had strictly pragmatic character and were devoided of philosophical and historiosophical thought. In my opinion this attitude calls for transformation as it is too superficial and leads to advanced generalizations.